Решите пример с алгебраическими дробями [latex] \frac{1}{m+2} +\frac{1}{m-2} - \frac{4}{ m^{2} - 4 } [/latex]

Решите пример с алгебраическими дробями [latex] \frac{1}{m+2} +\frac{1}{m-2} - \frac{4}{ m^{2} - 4 } [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{1}{m+2}+\frac{1}{m-2}-\frac{4}{m^2-4}=\frac{1}{m+2}+\frac{1}{m-2}-\frac{4}{(m-2)(m+2)}=\frac{m-2}{(m-2)(m+2)}+\frac{m+2}{(m-2)(m+2)}-\frac{4}{(m-2)(m+2)}=\frac{m-2+m+2-4}{(m-2)(m+2)}=\frac{2m-4}{(m-2)(m+2)}=\frac{2(m-2)}{(m-2)(m+2)}=\frac{2}{(m+2}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы